Revised species definitions and nomenclature of the rose colored Cithaerias butterflies (Lepidoptera, Nymphalidae, Satyrinae) - Penz, Carla M.; Alexander, Laura G.; Devries, Philip J. (Zootaxa, 2014)
This study provides updated species definitions for five rose-colored Cithaerias butterflies, starting with a historical overview of their taxonomy. Given their mostly transparent wings, genitalia morphology yielded the most reliable characters for species definition and identification. Genitalic divergence is more pronounced when multiple species occur in sympatry than between parapatric taxa. Cithaerias aurorina is granted full species status, C. cliftoni is reinstated as a full species, and one new combination is proposed, i.e. C. aurora tambopata. Two new synonyms are proposed, Callitaera phantoma and Callitaera aura = Cithaerias aurora.